Increasing Students’ Vocabulary Using Word Chain Game - Nuruddin, Habib; Saral, Diva Sayyidina; Hasanudin, Hasanudin (JOLIES : Journal of Linguistic and English Studies, 2026)
This study aimed to determine whether the use of the Word Chain Game could improve students’ vocabulary at the second grade of MTs Muhammadiyah 02 Aimas. The research applied a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. The participants of this study were 17 students. The data were collected through vocabulary tests, including a pre-test and two post-tests, to measure students’ improvement. The findings revealed a significant increase in students’ vocabulary mastery after the implementation of the Word Chain Game. The mean score of the pre-test was 43.05, which increased to 58.35 in the first post-test and reached 72.47 in the second post-test. Additionally, the percentage of students who achieved the minimum mastery criterion improved in each cycle. The results indicate that the Word Chain Game is an effective and engaging technique to enhance students’ vocabulary. It also encouraged students to participate actively and made the learning process more enjoyable. Therefore, the use of interactive games such as Word Chain Game is recommended for teaching vocabulary in English as a foreign language